The effects of problem-based learning on mathematical proficiency: A combined bibliometric analysis and meta-analysis review (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
The research goals are investigating the impacts of applying Problem-Based Learning (PBL) on mathematical proficiency. 23 primary research papers that met the inclusion assumptions were investigated in this study using a meta-analysis methodology. The Scopus database and UPI repository were used to identify empirical data. Additionally, the characteristics of publication year, strands of mathematical proficiency, geographic level, education level, and class level are examined in this study. The Comprehensive Meta-Analysis (CMA) application was employed to carry out the statistical computations, and the random effects model was followed throughout the calculation process. As a consequence, the overall of effect size is 0.77. Compared to traditional learning, the results showed that PBL implementation significantly improved students' mathematical proficiency. The analysis of moderator variables suggests that PBL works best when it is applied to strengthen the conceptual understanding and procedural fluency strands of mathematical proficiency. This discovery contributes valuable insights for the future implementation of PBL. Thus, these results recommend that collaborative studies among countries regarding the impact of Project-Based Learning will be crucial in the future to generate more comprehensive and inclusive results.